Evaluating of Digital Platforms Related Online Learning During Covid-19 Pandemic: Students' Satisfaction View - Sudung Nainggolan (AL-ISHLAH: Jurnal Pendidikan, 2021)
Various technology applications have been used in the teaching and learning process as a medium in the Covid-19 pandemic era to make the learning process easier. This study aims to determine the results of the evaluation of digital platforms for online learning systems that have been used during the covid-19 pandemic. Digital platforms a multimedia technology that facilitates online learning activities easily, especially during the current pandemic through the internet network. The research method used a qualitative descriptive cross-sectional. The subjects of the study were postgraduate students in Institute Injil Indonesia that were 90 students. The sample is taken using a simple random sample. Data were collected using questionnaires and interviews. The data were analyzed using data reduction, data presentation, and conclusion drawing. The results showed that students had a high level of satisfaction with Zoom as a digital platform in video conferencing and other digital platform applications that were considered satisfying, namely YouTube and Whatsapp. However, educators and some lecturers also like to use email for task collection activities during online learning activities during the covid-19 pandemic. The results of this study have implications for the development of digital applications for the management of online learning activities in the provision of paid video conferencing facilities for Institut Injil Indonesia.